Information and Decision Making in Judicial Public Policy: A Reflection from the Analysis of the Procedural Burden in Peru - Hernández Breña, Wilson (2009)
This paper aims to study the importance of procedural information to make decisions in judicial public policies in Peru and focuses on the existing perceptions on the procedural burden, the myths that feed the perceptions, the reality underlying the perceptions and the true sources of the procedural burden, all within the framework of the existing information on the Peruvian procedural burden. In the first part, the importance of information on the procedural burden and the relevance of its study is highlighted. Followed by this, the myths about the procedural burden and its consequences are developed and, finally, aspects that generate the procedural burden are identified in order that this information contributes to make appropriate decisions on the subject and increases the judicial efficiency. The theme developed in the work is highly innovative because it takes current information about the Peruvian procedural burden and, as a result, confirms or dismisses society's perceptions of the procedural burden. Along with this, it is a very original work because investigate a topic that is not developed or deepened in the Peruvian legal literature. Finally, it investigates an issue that, although it is not strictly legal, has repercussions in the legal field because it affects the correct judicial functioning and, as a result, affects the work of legal operators and the adequate protection of the rights of the people.